2013
DOI: 10.1080/09585176.2013.781388
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and developing student understandings of sustainable development

Abstract: There has recently been significant emphasis placed on environmental education through the United Nations’ Decade of Education for Sustainable Development (DESD). One of the aims of the DESD is to ‘prepare young people for a lifetime of sustainable living’, and yet, despite this, there is a lack of evidence to suggest whether or not the aims of ESD have been achieved within schools. This paper presents findings from a longitudinal study investigating one class of 14‐ and 15‐year‐old Geography students in Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Both of them recognise the environmental dimension most. This was the case among sixth and twelfth graders in Sweden (Berglund et al, 2014) and among UK geography students at the age of 14 and 15 [25,26]. However, Berglund and Gericke [27] found that when students deal with the dimensions separately, they give priority to social factors.…”
Section: Holistic Approaches To Sd In Esdmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of them recognise the environmental dimension most. This was the case among sixth and twelfth graders in Sweden (Berglund et al, 2014) and among UK geography students at the age of 14 and 15 [25,26]. However, Berglund and Gericke [27] found that when students deal with the dimensions separately, they give priority to social factors.…”
Section: Holistic Approaches To Sd In Esdmentioning
confidence: 99%
“…Student teachers in science and geography in UK studies [23,28], student teachers in New Zealand [29,30] Turkish science student teachers [31] and science and social science teachers in Sweden also recognise the environmental dimension the most. The economic dimension is less recognised by students [12,25] and students have vague perceptions of how economy is related to SD [27]. In line with students' conceptions of the economic dimension [27], teachers feel unsure about economic factors related to SD issues [31].…”
Section: Holistic Approaches To Sd In Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Kopnina, ), and other ways of understanding the relationships between the dimensions have been suggested (e.g. see Giddings et al, ; Walshe, ). However, during the 20 years following the Rio meeting, the three‐ring model was widely endorsed by international organizations such as UN, and has been adopted by national governments and organizations (Lehtonen, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A similar conclusion concerning tensions within the SD concept was drawn by Summers et al [36] in their study from UK. However, Walshe [37] found that during a one-year geography course in United Kingdom (UK), the students developed a more holistic view of SD and became more able to recognize tensions. Economic activities affect and are affected by social and environmental dimensions in an intertwined and dependent way.…”
Section: Holistic Approaches In Education For Sustainable Developmentmentioning
confidence: 99%